The Experiences of Canadian Women in Popular Music: “even on the worst sick no gas freezing canadian middle of january rockie mountain or halifax breakdown there is nothing better to do for a living” - MacKay, Robbie (Université Queen’s, 2008)
Keywords: Bibliographie; Nettoyer

Loyalty and Longevity in Audience Listening: Investigating Experiences of Attendance at a Chamber Music Festival - Pitts, Stephanie E.; Spencer, Christopher P. (Music and Letters, 2008)
There is currently much concern among arts organizations and their marketing departments that audiences for classical music are in decline, yet there has been little investigation so far of the experiences of long-term listeners that might yield insights into audience development and retention. This paper presents a case study of the Music in the Round chamber music festival, conducted over a three-year period that included the retirement of the host string quartet, the appointment of a new resident ensemble, and associated changes in audience attitudes and priorities. Questionnaire and interview data revealed the challenges faced by audience members in shifting their loyalty to a new ensemble and reappraising their own listening habits and stamina. The interaction between individual listening and collective membership of an audience is discussed, and the potential considered for understanding classical concert-goers as ‘fans’ or ‘consumers’.